Transforming Vocational Education Financing Governance through Performance-Based Hybrid Financing in Lampung Province - Junaina; Erlian Eka Damayanti; Undang Rosidin (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study analyzes the transformation of vocational education financing governance through performance-based and BLUD-based hybrid financing in Lampung Province. Using a descriptive qualitative design with a multisite case study approach, this study examined three vocational institutions with different governance characteristics: non-BLUD, developing BLUD, and large-scale BLUD schools. Data were collected through policy documents, school financial planning documents, institutional profiles, and relevant secondary data, and were analyzed using an interactive qualitative analysis model. The findings show that conventional financing remains highly dependent on government allocations and community contributions, creating fiscal vulnerability after the abolition of school committee fees. BLUD status strengthens financial autonomy by enabling schools to retain and reinvest revenue generated through Teaching Factory activities, industry partnerships, and production-based learning units. However, the effectiveness of this model depends on entrepreneurial leadership, performance-based budgeting, industrial collaboration, and digital accountability through ARKAS and SIPLah. This study implies that regional governments should accelerate BLUD readiness, strengthen vocational school financial management capacity, and develop hybrid financing policies that maintain a balance between institutional revenue generation, educational equity, and graduate quality improvement.